Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Walker, Peter J.; Siddell, Stuart G.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Adriaenssens, Evelien M.; Alfenas-Zerbini, Poliane; Davison, Andrew J.; Dempsey, Donald M.; Dutilh, Bas E.; García, María Laura; Harrach, Balázs; Harrison, Robert L.; et al. (Archives of virology, 2021)
This article reports the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2021. The entire ICTV was invited to vote on 290 taxonomic proposals approved by the ICTV Executive Committee at its meeting in October 2020, as well as on the proposed revision of the International Code of Virus Classification and Nomenclature (ICVCN). All proposals and the revision were ratified by an absolute majority of the ICTV members. Of note, ICTV mandated a uniform rule for virus species naming, which will follow the binomial 'genus-species' format with or without Latinized species epithets. The Study Groups are requested to convert all previously established species names to the new format. ICTV has also abolished the notion of a type species, i.e., a species chosen to serve as a name-bearing type of a virus genus. The remit of ICTV has been clarified through an official definition of ‘virus’ and several other types of mobile genetic elements. The ICVCN and ICTV Statutes have been amended to reflect these changes.